Influence of resistance to use, perceived ease of use, perceived usefulness, and facilitating conditions in the intention to use telemedicine in Peru - Jorge Ludeña-Poma; Sara Rojas-Gallegos; Leslye Solano-Ortiz; Yanira Castro-Chavez; Diana Chahua-Borda; Janeth Ludeña-Poma (Pensoft Publishers, 2024)
Telemedicine revolutionizes medical care by providing remote access to healthcare services, improving efficiency, reducing geographic barriers and providing timely, life-saving care for patients. Current research aims to evaluate the influence of resistance to use, facilitators to use, perceived ease of use and perceived usefulness of telemedicine on the intention to use telemedicine by citizens of Peru. The study collected responses from individuals in Peru through an online survey, and the data was analyzed by multivariate statistical techniques. The results showed that perceived ease of use had a positive and significant effect on perceived usefulness; then, perceived ease of use had a positive and significant effect on the intention to use telemedicine. Also, resistance to use did not have a significant effect on intention to use telemedicine. The bootstrapping analysis showed that the effects between the variables were statistically significant. The outcomes obtained may provide ideas to healthcare managers in public and private sectors for planning health programs based in telemedicine and can make diagnosis and treatments with remote patients.